Upregulated small GTPase immunity-associated proteins confer resistance to Neospora caninum in rat and bovine cells - Azam, Abdur Rehman; Mia, Md Mukthar; Bedwani, Julie; Witola, William H. (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundNeosporosis is a leading cause of abortions and neonatal mortality resulting in significant global economic losses in cattle production, and is also a common cause of a fatal neuromuscular degenerative disease in dogs, for which there are no effective treatments nor prophylactics available. Elucidation of Neospora-specific mechanisms that resistant hosts employ to orchestrate defenses against the parasite could hold the key to unveiling novel strategies for developing effective control approaches against neosporosis. Previously, we reported that the Lewis rat resists intracellular Toxoplasma gondii growth by augmenting the expression of GTPase Immunity-Associated Proteins (GIMAPs), namely GIMAP 4, 5, and 6 that mediate the resistance phenotype.MethodsHerein, we investigated the effect of upregulated expression of GIMAPs on the growth and proliferation of Neospora caninum (an evolutionarily close relative to T. gondii) in rat and bovine cells. First, we used two rat strains (Lewis and Brown Norway rats) to determine the effect of N. caninum infection on GIMAPs expression, and the ability of parasite proliferation in the respective rat cells and tissues. We analyzed the effect of GIMAP 4, 5 and 6-induced upregulation in permissible rat and bovine macrophages on N. caninum growth, and determined the molecular networks engaged by GIMAPs in orchestrating intracellular parasite killing.ResultsWe found that, unlike the Brown Norway rat, the Lewis rat is refractory to N. caninum infection, with a concomitant augmentation of GIMAP 4, 5 and 6 expression in response to infection. Corroboratively, overexpression of GIMAP transgenes in a N. caninum-permissive rat macrophage cell line induced accumulation of LAMP 1 (lysosome marker protein) on the parasitophorous vacuole membrane (PVM), resulting in vacuole acidification and restriction of N. caninum proliferation. Further, we found that bovine GIMAP 4, 5 and 6 are orthologous to rat GIMAPs, with a conserved AIG1 domain. Intriguingly, overexpression of bovine GIMAP transgenes in a N. caninum-susceptible bovine macrophage cell line inhibited intracellular proliferation of the parasites. DiscussionCollectively, our findings imply that upregulation of GIMAP 4, 5, and 6 mediate robust refractoriness to N. caninum through induction of lysosomal fusion to the otherwise non-fusogenic PVM, resulting in vacuole acidification and destruction of intracellular parasites.